Credit, indebtedness and speculation in Marx's political economy - Miguel D. Ramírez (Economic Thought, 2019)
This paper contends that Marx develops in Volume III of Capital an incisive conceptual framework in which excessive credit creation, indebtedness and speculation play a critical and growing role in the reproduction of social capital on an extended basis; however, given the decentralised and anarchic nature of capitalist production, the credit system does so in a highly erratic and contradictory manner which only postpones the inevitable day of reckoning. The paper also highlights Marx's relatively neglected but highly important analysis of the separation of ownership from management in the advanced capitalism of his day, England, and its modern-day implications for excessive risk-taking and debt-fuelled speculation up until the eve of the crash. More importantly, the paper argues that in Volumes II and III, Marx implicitly connected the expanding role of credit (which he associated with the development of capitalism) to a significant reduction in the turnover period of capital, thereby boosting the rate of surplus-value, and countering in a highly erratic and contradictory manner, the fall in the rate of profit. The growing role of credit has been relatively ignored in the Marxian literature as an important counteracting factor to the law of the declining rate of profit. It is not mentioned at all by Marx in his famous Chapter XIV, Vol. III of Capital where he discusses other important counteracting forces to the falling rate of profit, nor by Engels (in this particular context) who edited both Volumes II and III.
Keywords: B10; B14; B24; 330; bills of exchange; capital; credit; crises; fictitious capital; industrial (business) cycle; speculation; turnover period of capital